'Neknomination': Predictors in a sample of UK university students. (June 2015) - Moss, Antony C.; Spada, Marcantonio M.; Harkin, Jamila; Albery, Ian P.; Rycroft, Nicola; Nikčević, Ana V.
Abstract: Objectives: To identify prevalence and predictors of participation in the online drinking game 'neknomination' amongst university students. Method: A convenience sample of 145 university students participated in a study about drinking behaviours, completing a questionnaire about their participation in neknomination, the Alcohol Use Disorders Identification Test, and the Resistance to Peer Influence Scale. Results: Out of 145 students sampled, 54% took part in neknomination in the previous month. Mann–Whitney U tests revealed significantly higher scores on the Alcohol Use Disorders Identification Test, and significantly lower scores on the Resistance to Peer Influence Scale, for those who had participated in neknomination. A significant correlation was also shown between specific peer pressure to neknominate, and engagement in neknomination. A logistic regression analysis indicated that scores on the Alcohol Use Disorders Identification Test, but not the Resistance to Peer Influence Scale, predicted classification as an individual who participated in neknomination. Conclusions: We found that over half of respondents had participated in a neknomination game in the past month, with almost all male respondents having done so. Participation in neknomination was strongly associated with general hazardous drinking behaviour but not with resistance to peer influence. Further research is needed to understand the role of engagement with social media in drinking games and risky drinking. Highlights: First study to investigate the prevalence of 'neknomination' amongst UK university students Over half of the sample took part in neknomination in the previous month. Levels of alcohol use, lower resistance to peer influence, and being male predicted participation in neknomination.